Formas de equilíbrio e geologia de objetos transnetunianos - Branco, Hely Cristian (2020)
Transneptunian Objects (TNOs) are small bodies of the Solar System; they can be seen as spinning bodies under the influence of self-gravity, spin-related forces and tidal forces, classically considered to have fluid behaviour and, therefore, assume fluid equilibrium shapes. However, they are composed by geological materials that rarely behaves as fluids; thus, the use of geological criteria to analyse the shapes assumed by these objects when in equilibrium, i.e. their equilibrium shape, is required, resulting in more accurate understanding of their nature. This work proposes using the method described by Holsapple (2004) to evaluate the equilibrium state of small bodies. The TNOs Haumea, Quaoar and 2003 VS2, the centaurs Chariklo and 2002 GZ32, and the asteroids Ceres, Vesta and Lutetia were studied. Their shape (determined with high accuracy through the use of stellar occultations and data collected by space probes), rotation period and density (whenever available) were used to determine: i) if the object is in equilibrium; ii) if it presents fluid behaviour or if it has some type of internal resistance to deformation; and iii) the geological implications of this. In the absence of mass values, as is the case for 2003 VS2, Chariklo and 2002 GZ23, the method was used to infer the object’s density, under the assumptions that it presents fluid behaviour and is in equilibrium. All objects were found to be in equilibrium, but with shapes usually different than the fluid case (i.e. Maclaurin and Jacobi ellipsoids). It was shown that the material’s behaviour is an indicative of the possible internal composition and structure of an object, what is closely related to geological processes that took and are taking place on it; it allows the understanding, at least in general terms, of their geological history and evolution through the use of models and analogs. In addition to that, TNOs and other icy worlds present unique environments, very different than anything on Earth; they can be seen as huge real-life laboratories, possibly containing a vast number of geological processes unique to them and capable of changing some of the current paradigms of this field of science.